Synthesis and evaluation of antimalarial agents as inhibitors of plasmodium falciparum calcium-dependent protein kinases - Seanego, Tswene Donald (My University, 2019)
The world suffers under a serious threat of malaria with about 584 000 deaths reported each year and most of these fatalities being children under five years of age. Malaria is caused by the protozoan parasite of the genus Plasmodium. Five different malaria species infect humans and cause disease: P. vivax, P. malariae, P. ovale, P. knowlesi and the cause of most malaria deaths, P. falciparum. Several drugs have been used for the treatment of malaria since the 17th century. The drugs in use act on different stages of the malaria life cycle. However, most antimalarial drugs target the asexual stage of malaria, but not the gametocytes. Hence, new strategies are urgently needed to disrupt parasite reproduction, thus breaking the malaria life cycle. Studies have shown that calcium-dependent protein kinases (CDPKs) are an attractive drug target because of their uniqueness to plants and apicomplexans. Since the CDPKs are absent from humans (host), this makes them a potential target for drug development. Plasmodia species have five CDPKs that share the characteristic domain architecture of plant CDPKs, and studies have shown that these CDPKs play a vital role in various stages of the life cycle of plasmodia and other apicomplexan parasites. Pyrrolo[2,3-d]pyrimidine and pyrimidine are two of the most important heterocycles commonly found in natural products and medicinal products. These two scaffolds have received much attention from researchers and found applications in several areas of pharmaceutical and agrochemical research. Studies have shown that P. falciparum CDPK1 (PfCDPK1) is involved in the regulation of parasite motility and controls zygote development and transmission, while PfCDPK4 is required for male gametocyte exflagellation and sexual reproduction of the parasite. The work detailed in this PhD involved three aspects of research. The first part of this project involved using the recently solved X-ray crystal structure of PfCDPK4 to design inhibitors with either a pyrrolo[2,3-d]pyrimidine or branched pyrimidine scaffold. Flexible docking protocols were developed and compounds displaying the best binding interactions were synthesised. The second part of this thesis involved the synthesis of pyrrolo[2,3-d]pyrimidine derivatives that are potential inhibitors of PfCDPK4 and PfCDPK1. These novel compounds were characterised by NMR spectroscopy (where possible) and high resolution mass spectrometry (HRMS) and tested in a whole cell antiplasmodium assay. The most promising compound of this series was 5(2-ethoxynaphthalen-6-yl)-7-(2-morpholinoethyl)-7H-pyrrolo[2,3-d]pyrimidin-4-amine, which exhibited antimalarial activity in the low micromolar range (IC50 = 8.2 μM). The third part of this PhD project involved the synthesis of branched pyrimidine analogues in an attempt to identify a simpler scaffold for the development of kinase inhibitors. We have successfully managed to prepare a library of 10 analogues containing the pyrimidine ring. Sequential mono nucleophilic displacement followed by a sealed tube reaction and final Sonogashira cross coupling reaction allowed for the smooth preparation of these branched pyrimidine analogues. Once again, the antimalarial activity of the compounds prepared was assessed in an in vitro P. falciparum screen on the drug sensitive strain. N4-(Cyclopropylmethyl)5-[2-(2-methoxyphenyl)ethynyl]pyrimidine-4,6-diamine was the only compound in this series to display antimalarial activity (IC50 = 21.1 μM).
A thesis submitted to the Faculty of Science, University of the Witwatersrand Johannesburg in fulfillment of the requirements for the Degree of Doctor of Philosophy, March 2019